The USA National Phenology Network's Buffelgrass Green‐up Forecast map products. Issue 4 (12th November 2021) - Gerst, Katharine L.; Crimmins, Theresa M.; Posthumus, Erin; Marsh, R. Lee; Switzer, Jeff; Wallace, Cynthia
Abstract: Buffelgrass ( Cenchrus ciliaris syn. Pennisetum ciliare ) was introduced to Sonoran Desert in the early 20th century and has become widespread at low elevations. This perennial bunchgrass accumulates abundant biomass that can carry fires through ecosystems not adapted to fire, resulting in devastating impacts for native cacti and other plant and animal life. Buffelgrass is most effectively managed through the application of herbicide when the grass is at least 50% green. Because the grass rapidly greens up following summer monsoon rainfall, it is possible to forecast green‐up using daily rainfall measurements. In 2019, the USA National Phenology Network (USA‐NPN) released daily Buffelgrass Green‐up Forecast maps for the state of Arizona based on the PRISM 4 km daily total precipitation product. The daily digital Buffelgrass Green‐up Forecast maps are a freely available data product and meet the FAIR principles of findability, accessibility, interoperability and reusability. They are permanently archived and publicly accessible as raster and image layers from the USA‐NPN website. These map layers support planning the timing of management activities to maximize buffelgrass treatment efficacy and researchers seeking to incorporate daily estimates of buffelgrass greenness in their analyses. Abstract : The USA National Phenology Network's Buffelgrass Green‐up Forecast for September 20, 2021. Locations in green are predicted to achieve >50% green‐up in 1–2 weeks, enabling treatment with herbicide. These maps support planning the timing of management activities to maximize buffelgrass treatment efficacy. Spanish Abstract: Cenchrus ciliaris (syn Pennisetum ciliare, Buffelgrass) fue introducido en el desierto de Sonora a principios del siglo XX y ahora se distribuye ampliamente en las elevaciones bajas. Este pasto racimoso perenne acumula abundante biomasa que puede transportar incendios a través de ecosistemas que no son adaptados al fuego, lo cual resulta en tremendos impactos para los cactus nativos y otros plantas y animales. C. ciliaris se controla de manera más efectiva mediante la aplicación de herbicidas cuando el pasto es al menos 50% verde. Debido a que la hierba reverdece rápidamente después de las lluvias monzónicas de verano, es posible pronosticar el reverdecimiento utilizando mediciones de lluvia diaria. En 2019, la Red Nacional de Fenología de EE. UU. (USA‐NPN) publicó pronósticos ecológicos de C. ciliaris para el estado de Arizona basados en el producto de precipitación total diaria de 4 km de PRISM. Los pronósticos ecológicos están disponibles gratuitamente y cumplen con los principios FAIR de búsqueda, accesibilidad, interoperabilidad y reutilización. Se archivan permanentemente y son disponibles como imágenes y rásteres desde el sitio web de la USA‐NPN. Los pronósticos apoyan a la planificación de las actividades de manejo para maximizar la eficacia del tratamiento del pasto C. ciliaris y los investigadores que buscan incorporar estimaciones diarias del verdor del pasto C. ciliaris en sus análisis.